Automatic System For Utility Electrical Fault (Fault Location Detection Using Labview) - Mohd Firdaus Bin Noordin, Mohd Firdaus (2010)
Software called LabVIEW is used to develop the system that can detect the location of permanent fault in a domestic electrical wiring system. The idea is when the location of fault is determined, an automatic system to isolate the Miniature Circuit Breaker (MCB) that has fault can be eveloped. So when the MCB that has fault has been isolated, the ELCB can be turned on without tripping again.